The clinical outcomes of extended resections in patients with IV stage gallbladder cancers: A retrospective study from a large tertiary center - Zhang, Kecheng; Liu, Hu; Zhao, Yongyang; Zhang, Baohua (Frontiers in Oncology, 2022)
Background and aim The role of extended resections in patients with clinical stage IV gallbladder cancer (GBC) remains unclear. This study retrospectively analyzed the clinical outcomes of patients who underwent extended resections for IV GBC. Methods Patients who were diagnosed with IV stage GBCs and underwent extended resections in Eastern Hepatobiliary Surgery Hospital, Shanghai, China, were retrospectively included in our study. Extended resection was defined as a major hepatectomy (resection of ≥3 liver segments), a pancreatoduodenectomy, or both. The clinical outcomes (baseline characteristics, preoperative variables, intraoperative variables, pathological outcomes, and follow-up data) were obtained and analyzed. The factors associated with major postoperative complications and long-term survival were analyzed by logistic regression analyses. Results From January 2011 to June 2017, 74 patients were included in our study. There were 33 (44.6%) males and the median age was 62.5 years (interquartile range [IQR], 56.0-67.0 years). According to pathological specimens, the median tumor size was 7cm (IQR, 6-8cm), 73(98.6%) of them received R0 resection and 72 (97.2%) of them were IV A stage GBC. Three perioperative deaths (5.4%) occurred, and major postoperative complications occurred for 15 patients (20.3%). Among them, 61 patients (82.4%) experienced recurrence and 17 patients (23.0%) were still alive after a median follow-up period of 52 months. The disease free survival time was 9 months (95% confidence interval [CI], 7.8-10.2 months) and the overall survival was 18.0 months (95% CI, 15.2-20.8 months). Longer hospital stay days [odds ratio, (OR)=1.979, 95%CI:1.038-1.193, P=0.003), initial symptoms with abdominal pain (OR=21.489, 95%CI=1.22-37.57, P=0.036), more blood transfusion volume during hospitalization (OR=1.036, 95%CI:1.021-1.058, P=0.005), and intraoperative hemorrhage (OR=18.56, 95%C:3.54-47.65, P=0.001) were independently associated with postoperative complications. Moreover, locally recurrence (OR=1.65, 95%CI:1.17-1.96, P=0.015), and more adjuvant chemotherapy cycles (OR=1.46, 95%CI:1.13-1.76, P=0.026) were independently associated with long-term survival. Conclusion Our retrospective study identified that extended resections can be safely and efficaciously performed on stage IV GBC patients in selected cases and performed by experienced surgeons.